Low Wage of Civil Servant and National Cultures: How They Relate to Corruption? - Suntharanurak, Sutthi (Journal of Applied Economics and Management Strategy, 2018)
This paper discussed two determining factors of corruption which are (1) low wage of civil servants and (2) national cultures. The author emphasized on the causal relationship between corruption and these two variables. This paper showed how to measure the corruption behavior and how to quantify the national cultures. Also it proposed fair wage-corruption model which it can be argued that low wages of civil servants could be explained as the cause of corruption. Furthermore, the author proposed three theoretical models which explained the relationship of corruption, namely low wage of civil servant and national cultures.